Resistance against Women’s Objectification Portrayed in Zora Neale Hurston’s Their Eyes Were Watching God - Made Dian Ratnawati; Mala Hernawati (Universitas Gadjah Mada, 2020)
In the early twentieth century, African-American women in the southern United States faced double oppression as a result of patriarchy and racism. They strive to reclaim their independence, all the more so when they are bound by their marriage. Their Eyes Were Watching God (1937) is Zora Neale Hurston's magnum opus, which chronicles the objectification of a young African-American woman called Janie Crawford during her marriage. Through the lens of Black Feminism, this research aims to identify the many forms of female objectification present in the novel and to ascertain the responses taken by the main character in response to the objectification. This research makes use of Martha Nussbaum's and Rae Langton's objectification ideas. Additionally, this study employs Kumea Shorter-Gooden's resistance strategies to evaluate the main character's strategies for resisting objectification. Janie Crawford was subjected to nine distinct forms of objectification by both her first and second husbands, Logan and Jody, according to this study. Additionally, this research illustrates how Janie Crawford's opposition to objectification is fueled by the concept of self-definition. In general, the findings indicate that the novel is centered on the problem of women's objectification and is a timely representation of African American women's lives in the early twentieth century.